How do European Mature Adults and Elderly Perceive SARS-COV-2 and Associated Control Measures? A Cross-Country Analysis of Mental Health Symptoms in June and July 2020 - Julian Perelman; Julian Perelman; Miguel Xavier; Miguel Xavier; Miguel Xavier; Pedro Pita Barros (International Journal of Public Health, 2022)
Objectives: Recent literature points out that elderly people are psychologically resilient to COVID-19, but the studies were performed in specific contexts. We measured the link between the worsening of mental health symptoms, the epidemiologic situation, and control measures among European people aged 50 or older.Methods: We used data from the 2020 wave of SHARE, merged with Oxford COVID-19 Government Response Tracker data (n = 38,358). We modeled the risk of worsening of depression, anxiety, sleeping trouble, and loneliness symptoms’ self-perception, as functions of control measures and 7-days death incidence, using logistic regressions.Results: The worsening of anxiety and depression perception were more common (16.2 and 23.1%, respectively), compared to that of sleeping troubles and loneliness (8.1 and 11.5%, respectively). The worsening of depression and anxiety perception was negatively related to the rigor of control measures. The seven-days death incidence was positively linked to all symptoms except sleeping troubles.Conclusion: Older people were the most exposed to death risk and were affected psychologically by the COVID-19 epidemiological situation; yet control measures were protective (or neutral) to their mental health condition.